Effect of human growth hormone (hGH) on growth promotion in juvenile catfish, Heteropneustes fossilis (Bloch) - Nayak, P K; Mishra, J; Mishra, T K; Kumar, K; Ayyappan, S (Indian Journal of Fisheries, 2011)
The ability of human growth hormone (hGH) to accelerate the growth of juvenile catfish, H. fossilis was investigated and the potential of bath/immersion as a method of exogenous administration of growth hormone was assessed. Administration of hGH by immersion at different dosages for 4 hours at every 5 days interval resulted in a significant increase in specific growth rate (SGR) as compared to controls during the four week treatment period. A significant decrease in specific growth rate was observed during 4-8 week post-treatment period as compared to the treatment period. The effect of 7 Î¼g/1 hGH was minimal and the effect of 14 Î¼g/l hGH was higher compared to other hGH treated groups. A comparison of immersed versus non-immersed and sham-immersed controls indicated that immersion protocol accelerated the growth in H. fossilis juveniles.